Porous nickel-iron hydrotalcite adsorbent as well as preparation method and application thereof
By dropping the mixture of Ni2+ and Fe3+ salts into the aqueous amide solution, the amide-assisted coprecipitation reaction is carried out to prepare porous nickel-molecule hydrotalcite adsorbent, which solves the problems of low fluorine removal capacity and complex process of existing hydrotalcites, and achieves efficient and stable fluorine ion removal.
Patent Information
- Application Number
- CN202411861484.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-14
AI Technical Summary
The existing modified hydrotalcite has low fluorine removal capacity, complex preparation process, high energy consumption and poses risks to human health.
Porous nickel molten hydrotalcite adsorbent is prepared by dropwise adding a mixed solution of soluble Ni2+ and Fe3+ salts to the aqueous amide solution, controlling the pH value to 8-12, and carrying out amide-assisted coprecipitation reaction. This method does not require secondary calcination activation or anion replacement, simplifies the process and reduces energy consumption.
The obtained porous nickel hydrotalcite adsorbent has an excellent fluorine removal capacity, can effectively remove fluorine ions under low concentration and near neutral conditions, far better than the performance of commercial alumina fluorine removal agents, and has a stable structure, which is suitable for repeated recycling.
Smart Images

Figure CN119612608A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of defluorination agent materials, and in particular to a porous nickel-iron hydrotalcite adsorbent and a preparation method and application thereof. Background Art
[0002] The high-concentration fluoride ion removal technology used in practice is mainly the pharmaceutical method (such as calcium salt precipitation and aluminum salt flocculation), but it can only reduce the fluoride ion concentration to about 10 mg / L, which is much higher than the 1.5 mg / L drinking water standard set by the World Health Organization. In order to obtain low-fluoride water, further defluoridation (deep defluoridation) is required on the basis of pretreatment with the pharmaceutical method. Among various methods, the adsorption method has attracted much attention due to its simple process, easy operation and low cost. Among them, the development of efficient fluoride ion adsorption materials is the key to achieving deep defluoridation.
[0003] Hydrotalcite, also known as layered double hydroxide (LDH), has a general chemical formula of [M 1-x 2+ M x 3+ (OH)2]x + (A n- ) x / n mH2O, where M 2+ and M 3+ are divalent and trivalent metal cations, respectively, located on the brucite layer; A n- is an interlayer anion, such as carbonate, nitrate, nitrate, phosphate, etc.; x is M 3+ / (M 2+ +M 3+ ) molar ratio; m is the molar amount of water molecules between layers. Hydrotalcite has the characteristics of interlayer anion exchange, size controllable, memory effect, etc., and is widely used in photoelectrocatalysis, adsorption, functional materials and medicine. In addition, since the metal layer of LDH is positively charged, it is particularly suitable as an adsorbent to remove anions in water, and the synthesis of LDH is relatively easy and economical.
[0004] In recent years, LDH has also been used to remove fluorine. Among them, Al is a trivalent metal element and other monovalent or divalent metals are cations. This is a type of LDH that has been studied more. Among them, MgAl-LDH is the first LDH used to remove fluorine ions and is currently the most widely studied. In addition, CaAl-LDH, which is composed of Ca and Al, can release Ca in the process of removing fluorine. 2+ Complexing with fluoride ions increases the fluoride removal capacity. However, both types of LDH may release Al ions during use, which may pose a risk to human health. Therefore, the development of LDH without trivalent Al is an important research direction.
[0005] Fe is widely available and harmless to the human body, so it can be used to synthesize M3+ For example, MgFe-LDH can be synthesized by coprecipitation or hydrothermal method, but its maximum defluorination capacity after thermal activation modification is only 50.91 mg / g; high-crystallinity NiFe-LDH synthesized by high-temperature solvent method has a theoretical maximum adsorption capacity of 248.44 mg / g, but its preparation method includes cumbersome anion replacement and high-energy calcination steps, and the production cost is relatively high. Summary of the invention
[0006] The present invention provides a porous nickel-iron hydrotalcite adsorbent and a preparation method and application thereof, which effectively solve the technical problems of low fluorine removal capacity, complex preparation process, high energy consumption and risk to human health of the existing modified hydrotalcite, and also provides a nickel-iron hydrotalcite adsorbent with a porous layered structure.
[0007] The first object of the present invention is to provide a method for preparing a porous nickel-iron hydrotalcite adsorbent, comprising the following steps:
[0008] In a protective atmosphere, add soluble Ni to the amide aqueous solution at 50-95°C. 2+ Salt and soluble Fe 3+ The mixed solution of salts is prepared, the pH value is controlled to be 8-12, and an amide is used to perform an auxiliary coprecipitation reaction to obtain a porous nickel-iron hydrotalcite adsorbent.
[0009] As a preferred embodiment, before the coprecipitation reaction occurs, the aqueous amide solution and the mixed solution are treated with nitrogen for ≥30 min respectively.
[0010] As a preferred embodiment, the amide and soluble Ni 2+ Salt and soluble Fe 3+ The molar ratio of the sum of the salts is 2.5 to 50:1. Specifically, the concentration of the amide aqueous solution is 5 to 10 mol / L, and the Ni 2+ and Fe 3+ The total concentration is 0.2-2 mol / L, and the volume ratio of the amide aqueous solution to the mixed solution is 1:1.
[0011] As a preferred embodiment, the soluble Ni 2+ Salt and soluble Fe 3+ The molar ratio of the salt is 1 to 5:1.
[0012] As a preferred embodiment, the coprecipitation reaction time is 5 to 20 minutes.
[0013] As a preferred embodiment, the soluble Ni 2+ The salt is nickel nitrate or nickel chloride, the soluble Fe3+ The salt is ferric nitrate or ferric chloride; the amide is formamide, acetamide or N,N-dimethylformamide.
[0014] As a preferred embodiment, the pH value is regulated by using a 2.5M NaOH solution.
[0015] As a preferred embodiment, after the coprecipitation reaction is completed, centrifugation is performed to obtain a primary product, the primary product is washed with ethanol and deionized water, and dried at 70° C. to 80° C. to obtain a porous nickel-iron hydrotalcite adsorbent.
[0016] As a preferred embodiment, after the reaction is completed, the centrifuged sample is washed with ethanol and deionized water and dried at 80° C. to obtain a porous nickel-iron hydrotalcite adsorbent.
[0017] The second object of the present invention is to provide a porous nickel-iron hydrotalcite adsorbent prepared by the above preparation method.
[0018] The third object of the present invention is to provide a use of the porous nickel-iron hydrotalcite adsorbent in removing fluoride ions in water.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] In the present invention, soluble Ni is added dropwise to an amide aqueous solution at 50-95°C in a nitrogen atmosphere. 2+ Salt and soluble Fe 3 + A mixed solution of salts, while controlling the pH value to be 8-12, is subjected to an auxiliary coprecipitation reaction by amide to obtain a porous nickel-iron hydrotalcite adsorbent. The present invention uses amide molecules to form ligands with metal ions and embed them in the hydrotalcite layer, which are removed during the heating and cleaning process to form a porous structure; in addition, the amide molecules help to slow down the overly tight stacking between the hydrotalcite sheets, so that the synthesized porous nickel-iron hydrotalcite adsorbent has more adsorption sites, thereby enhancing its defluorination capacity for fluoride ions in the water body. Compared with the existing known hydrotalcite defluoridation agent preparation technology, the present invention does not require secondary calcination activation or secondary anion replacement, and a porous nickel-iron hydrotalcite adsorbent with better defluorination capacity can be obtained in one step.
[0021] The present invention performs nitrogen-gas-exhausted air treatment on the amide aqueous solution and the mixed solution before the coprecipitation reaction, thereby greatly reducing the carbonate or bicarbonate formed by the dissolution of carbon dioxide in the atmosphere and entering the interlayer of the hydrotalcite, thereby effectively reducing the risk of weakening the defluorination performance of the porous nickel-iron hydrotalcite adsorbent, and further ensuring the efficient defluorination ability and quality stability of the porous nickel-iron hydrotalcite adsorbent of the present invention.
[0022] The present invention uses a synthesized porous nickel-iron hydrotalcite adsorbent for fluoride ion adsorption, and realizes a porous structure of the adsorbent by adding amide. The porous nickel-iron hydrotalcite adsorbent provided by the present invention shows excellent defluorination activity in low-concentration, near-neutral fluorine-containing water bodies. Under the conditions of 5g / L and pH=6, the fluoride ion concentration of 10mg / L can be reduced to 0.8mg / L, which is much better than the defluorination performance of commercial alumina defluorinating agent under the same conditions. In addition, the defluorinating agent is used under near-neutral conditions, so it can maintain structural stability for a long time and is suitable for repeated recycling. The addition of amide molecules in the preparation process of the present invention does not affect the layered structural characteristics of the porous nickel-iron hydrotalcite, and the porous hydrotalcite prepared using amide has a balanced defluorination capacity of 10.32mg / g, which is much larger than the defluorination capacity (4.94mg / g) of the hydrotalcite prepared without using amide molecules. This is because the addition of amide molecules forms a porous material structure, which makes the fluoride ion transmission faster, and also gives the adsorbent material more active sites that can adsorb fluoride ions. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 X-ray diffraction patterns of the porous nickel-iron hydrotalcite adsorbent prepared in Example 1 of the present invention, the nickel-iron hydrotalcite adsorbent prepared in Comparative Example 1 (without adding amide pore-forming agent), and the nickel-iron hydrotalcite adsorbent prepared in Comparative Example 2 (without introducing nitrogen to control carbonate ions).
[0024] Figure 2 Fourier transform infrared spectra of the porous nickel-iron hydrotalcite adsorbent prepared in Example 1 of the present invention, the nickel-iron hydrotalcite adsorbent prepared in Comparative Example 1 (without adding amide pore-forming agent), and the nickel-iron hydrotalcite adsorbent prepared in Comparative Example 2 (without introducing nitrogen to control carbonate ions).
[0025] Figure 3 This is a transmission electron microscopy image of the porous nickel-iron hydrotalcite adsorbent prepared in Example 1 of the present invention; wherein, Figure a is a TEM morphology image at a lower magnification, and Figure b is a TEM morphology image at a high magnification.
[0026] Figure 4 The fluoride removal rate of the porous nickel-iron hydrotalcite adsorbent prepared in Example 1 of the present invention in water bodies with different pH values is shown in FIG. 1 when the dosage is 2 g / L, the fluoride removal time is 6 h, the temperature is 30° C., and the initial concentration C0 of the fluoride ion solution is 10 mg / L.
[0027] Figure 5 The graph is a graph of fluorine removal rates of the porous nickel-iron hydrotalcite adsorbent prepared in Example 1 of the present invention at different dosages under the conditions of pH 6, defluorine removal time of 6 h, temperature of 30° C., and initial concentration of fluorine ion solution of 10 mg / L.
[0028] Figure 6The figure is a comparison chart of the defluorination performance of the porous nickel-iron hydrotalcite adsorbent prepared in Example 1 of the present invention in fluorine-containing water bodies with different initial concentrations when the dosage is 2 g / L, the defluorination time is 6 h, the pH value is 6, and the temperature is 30°C.
[0029] Figure 7 This figure shows the influence of other coexisting anions in the water body on the fluorine removal performance of the porous nickel-iron hydrotalcite adsorbent prepared in Example 1 of the present invention under the conditions of a dosage of 2 g / L, a fluorine removal time of 6 h, a temperature of 30°C, and an initial concentration C0 of the fluoride ion solution of 10 mg / L.
[0030] Figure 8 The present invention is a graph comparing the fluorine removal efficiencies of the porous nickel-iron hydrotalcite adsorbent prepared in Example 1 of the present invention, the nickel-iron hydrotalcite adsorbent prepared in Comparative Example 1 (without the addition of an amide pore-forming agent), the nickel-iron hydrotalcite adsorbent prepared in Comparative Example 2 (without the introduction of nitrogen to control carbonate ions), and commercial activated alumina under the conditions of a dosage of 5 g / L, a fluorine removal time of 3 h, a temperature of 30°C, and an initial fluoride ion solution concentration C0 of 10 mg / L. DETAILED DESCRIPTION
[0031] In order to enable those skilled in the art to better understand the technical solution of the present invention and implement it, the present invention is further described below in conjunction with specific embodiments and drawings, but the embodiments are not intended to limit the present invention. The following test methods and detection methods, unless otherwise specified, are conventional methods; the reagents and raw materials, unless otherwise specified, are commercially available.
[0032] In view of the above mentioned background technology: First, MgAl-LDH and CaAl-LDH composed of Ca and Al for removing fluoride ions may release Al ions during use, which may pose a risk to human health, and this method of defluorination may bring secondary pollution risks; Second, MgFe-LDH is synthesized by coprecipitation or hydrothermal method, but its maximum defluorination capacity after thermal activation modification is only 50.91 mg / g, which is too small; Third, high-crystallinity NiFe-LDH synthesized by high-temperature solvent method has a theoretical maximum adsorption capacity of 248.44 mg / g, but its preparation method includes cumbersome anion replacement and high-energy calcination steps, and the production cost is relatively high. In view of the above three technical problems, the present invention provides a porous nickel-iron hydrotalcite adsorbent and its preparation method and application.
[0033] The technical solution of the present invention is analyzed and explained in detail below.
[0034] The present invention first provides a method for preparing a porous nickel-iron hydrotalcite adsorbent, comprising the following steps:
[0035] In a protective atmosphere, add soluble Ni to the amide aqueous solution at 50℃~95℃ 2+ Salt and soluble Fe 3+ The mixed solution of salts is simultaneously added with 2.5M NaOH solution within 10 minutes, the pH value is controlled to be 8-12, and an amide is used to assist the coprecipitation reaction. After the coprecipitation reaction is completed, centrifugation is performed to obtain a primary product, and the primary product is washed with ethanol and deionized water, and dried at 70°C-80°C to obtain a porous nickel-iron hydrotalcite adsorbent.
[0036] For the above-mentioned temperature range of 50°C to 95°C, if the reaction temperature is too high, above 100°C, since the reaction is an open system, water will evaporate quickly, otherwise a high-pressure reactor will be required, and the production cost will increase; if the temperature is too low, a longer time will be required, which will slow down the production efficiency and deteriorate the crystallinity of the hydrotalcite.
[0037] For the above pH value of 8 to 12, if the pH is too low, OH - If the concentration is insufficient, metal ions cannot be effectively precipitated, resulting in difficulty in forming hydrotalcite or low crystallinity. If the pH is too high, it will cause the formation of other by-products (such as metal oxides or hydroxides), affecting the purity and crystallinity of the hydrotalcite.
[0038] In the above technical solution, amide molecules are used to form ligands with metal ions and are embedded in the hydrotalcite layer, and are removed during the subsequent heating and cleaning process to form a porous structure; in addition, the amide molecules help to slow down the overly tight stacking of hydrotalcite sheets, so that the synthesized porous nickel-iron hydrotalcite adsorbent has more adsorption sites, thereby enhancing its defluorination capacity for fluoride ions in water.
[0039] It should be noted that the amide and soluble Ni 2+ Salt and soluble Fe 3+ The molar ratio of the sum of the salts is 2.5 to 50:1. Specifically, the concentration of the amide aqueous solution is 5 to 10 mol / L, and the Ni 2+ and Fe 3+ The total concentration is 0.2-2 mol / L, and the volume ratio of the amide aqueous solution to the mixed solution is 1:1. Because the amide molecule is a pore-forming agent, only when it matches the total amount of nickel and iron can it produce uniform pores on the nickel-iron hydrotalcite layer and maintain the physical phase of the nickel-iron hydrotalcite. If the amide concentration is too low (or the nickel-iron content is high), the pore-forming agent required for the hydrotalcite is insufficient, and it is impossible to obtain enough pores in the hydrotalcite; if the amide concentration is too high (or the nickel-iron content is low), the physical phase structure of the hydrotalcite will be directly destroyed.
[0040] It should be noted that the soluble Ni 2+ Salt and soluble Fe 3+The molar ratio of the salt is 1 to 5: 1. If it is not within this range, the iron content or nickel content may be too high, and iron or nickel hydroxide impurities may be formed while generating NiFe hydrotalcite, thereby reducing the adsorption amount.
[0041] In order to prevent carbon dioxide in the atmosphere from dissolving to form carbonate and bicarbonate, which would have a negative and sensitive effect on the defluorination performance of the hydrotalcite, the amide aqueous solution and the mixed solution were treated with nitrogen for ≥30 minutes before the coprecipitation reaction occurred, so as to effectively remove the risk of carbonate and bicarbonate on the weakened defluorination performance of the porous nickel-iron hydrotalcite adsorbent.
[0042] As a preferred embodiment, the coprecipitation reaction time is 5 to 20 minutes. When the time is too short, it is not enough to form hydrotalcite, and when it is longer than 20 minutes, the coprecipitation reaction is already over, and further increasing the time is not beneficial to increasing the product yield.
[0043] It should be noted that the soluble Ni 2+ The salt is nickel nitrate or nickel chloride, the soluble Fe 3+ The salt is ferric nitrate or ferric chloride; the amide is formamide, acetamide or N,N-dimethylformamide.
[0044] Through the above-mentioned preparation method, the present invention obtains a porous nickel-iron hydrotalcite adsorbent. The interlayer anion of the porous nickel-iron hydrotalcite adsorbent provided by the present invention is NO 3- and Cl - , Ni 2+ and Fe 3+ The molar ratio of ions can be controlled (1 to 5:1), and the formed hydrotalcite sheets contain micropores, which have a larger specific surface area and more active adsorption sites than traditional hydrotalcite.
[0045] The present invention applies the prepared porous nickel-iron hydrotalcite adsorbent to remove fluoride ions in water. When the fluoride ion concentration in the water is 10 mg / L, the additive amount of the porous nickel-iron hydrotalcite adsorbent is 5 g / L, and the pH value of the fluoride-containing water is 6, the best fluoride removal effect can be achieved.
[0046] The porous nickel-iron hydrotalcite adsorbent of the present invention can be used for defluorination, and fluoride ions in water bodies with a concentration lower than 10 mg / L can be effectively removed, meeting the World Health Organization's 1.5 mg / L and China's 1 mg / L drinking water standards; and the pH value during the defluorination process is controlled at a near-neutral pH of 6, which effectively reduces the corrosion and dissolution of the defluoridation agent itself by the acidic environment, reduces the secondary pollution of the water body by the hydrotalcite metal ions, and can also improve the recovery rate of the defluoridation agent.
[0047] The technical effects of the present invention are described below through specific embodiments and comparative examples.
[0048] Example 1
[0049] A method for preparing a porous nickel-iron hydrotalcite adsorbent comprises the following steps:
[0050] S1, prepare a 5.8 mol / L formamide aqueous solution, exhaust the air with nitrogen for 30 min, and heat to 80°C at the same time.
[0051] S2, using nickel nitrate and iron nitrate to prepare Ni 2+ and Fe 3+ The molar ratio is 3:1, Ni 2+ and Fe 3+ The mixed solution with a total concentration of 0.5 mol / L was purged with nitrogen for 0.5 h.
[0052] S3, according to the volume ratio of 1:1, the mixed solution was dripped into the formamide aqueous solution, and 2.5M sodium hydroxide solution was added to adjust the pH of the system to 10, and nitrogen was maintained. After the temperature was kept at 80°C for 10 minutes, the precipitate was separated by centrifugation, and the centrifuged sample was washed alternately with ethanol and deionized water, and dried at 80°C overnight to obtain a porous nickel-iron hydrotalcite adsorbent. Its XRD, FTIR and TEM are as follows Figure 1 , Figure 2 , Figure 3 shown.
[0053] Example 2
[0054] A method for preparing a porous nickel-iron hydrotalcite adsorbent comprises the following steps:
[0055] S1, prepare an 8 mol / L aqueous solution of acetamide, exhaust the air with nitrogen for 30 min, and heat to 90°C at the same time.
[0056] S2, using nickel chloride and ferric chloride to prepare Ni 2+ and Fe 3+ The molar ratio is 1:1, Ni 2+ and Fe 3+ The mixed solution with a total concentration of 0.7 mol / L was purged with nitrogen for 0.5 h.
[0057] S3, according to the volume ratio of 1:1, the mixed solution was added dropwise into the formamide aqueous solution, and 2.5M sodium hydroxide solution was added dropwise to adjust the pH value of the system to be stable at 12, nitrogen was maintained, the temperature was maintained at 90°C for 8 minutes, and the precipitate was separated by centrifugation. The centrifuged sample was washed alternately with ethanol and deionized water, and dried at 80°C overnight to obtain a porous nickel-iron hydrotalcite adsorbent.
[0058] Example 3
[0059] A method for preparing a porous nickel-iron hydrotalcite adsorbent comprises the following steps:
[0060] S1, prepare a 5 mol / L aqueous solution of N,N-dimethylformamide, exhaust the air with nitrogen for 30 min, and heat to 50°C at the same time.
[0061] S2, using nickel chloride and ferric chloride to prepare Ni 2+ and Fe 3+ The molar ratio is 5:1, Ni 2+ and Fe 3+ The mixed solution with a total concentration of 0.2 mol / L was purged with nitrogen for 0.5 h.
[0062] S3, according to the volume ratio of 1:1, the mixed solution was added dropwise into the formamide aqueous solution, and 2.5M sodium hydroxide solution was added dropwise to adjust the pH value of the system to 8, nitrogen was maintained, and the temperature was maintained at 50°C for 20 minutes, and the precipitate was separated by centrifugation. The centrifuged sample was washed alternately with ethanol and deionized water, and dried at 80°C overnight to obtain a porous nickel-iron hydrotalcite adsorbent.
[0063] Example 4
[0064] A method for preparing a porous nickel-iron hydrotalcite adsorbent comprises the following steps:
[0065] S1, prepare a 10 mol / L aqueous solution of acetamide, exhaust the air with nitrogen for 30 min, and heat to 95°C at the same time.
[0066] S2, using nickel chloride and ferric chloride to prepare Ni 2+ and Fe 3+ The molar ratio is 2:1, Ni 2+ and Fe 3+ The mixed solution with a total concentration of 2 mol / L was purged with nitrogen for 0.5 h.
[0067] S3, according to the volume ratio of 1:1, the mixed solution was added dropwise into the formamide aqueous solution, and 2.5M sodium hydroxide solution was added dropwise to adjust the pH value of the system to 9, nitrogen was maintained, and the temperature was maintained at 95°C for 5 minutes, and the precipitate was separated by centrifugation. The centrifuged sample was washed alternately with ethanol and deionized water, and dried at 80°C overnight to obtain a porous nickel-iron hydrotalcite adsorbent.
[0068] Example 5
[0069] A method for preparing a porous nickel-iron hydrotalcite adsorbent comprises the following steps:
[0070] S1, prepare a 7 mol / L aqueous solution of acetamide, exhaust the air with nitrogen for 30 min, and heat to 60°C at the same time.
[0071] S2, using nickel chloride and ferric chloride to prepare Ni 2+ and Fe 3+ The molar ratio is 4:1, Ni 2+ and Fe 3+ The mixed solution with a total concentration of 1.2 mol / L was purged with nitrogen for 0.5 h.
[0072] S3, according to the volume ratio of 1:1, the mixed solution was added dropwise into the formamide aqueous solution, and 2.5M sodium hydroxide solution was added dropwise to adjust the pH value of the system to be stable at 10, nitrogen was maintained, and the temperature was maintained at 60°C for 15 minutes, and the precipitate was separated by centrifugation. The centrifuged sample was washed alternately with ethanol and deionized water, and dried at 80°C overnight to obtain a porous nickel-iron hydrotalcite adsorbent.
[0073] Example 6
[0074] A method for preparing a porous nickel-iron hydrotalcite adsorbent comprises the following steps:
[0075] S1, prepare a 9 mol / L aqueous solution of acetamide, exhaust the air with nitrogen for 30 min, and heat to 70°C at the same time.
[0076] S2, using nickel chloride and ferric chloride to prepare Ni 2+ and Fe 3+ The molar ratio is 3:1, Ni 2+ and Fe 3+ The mixed solution with a total concentration of 1.6 mol / L was purged with nitrogen for 0.5 h.
[0077] S3, according to the volume ratio of 1:1, the mixed solution was added dropwise into the formamide aqueous solution, and 2.5M sodium hydroxide solution was added dropwise to adjust the pH value of the system to 9, nitrogen was maintained, and the temperature was kept at 70°C for 10 minutes, and the precipitate was separated by centrifugation. The centrifuged sample was washed alternately with ethanol and deionized water, and dried at 80°C overnight to obtain a porous nickel-iron hydrotalcite adsorbent.
[0078] In order to further illustrate the technical effect of the present invention, the present invention is also provided with a comparative example, as follows:
[0079] Comparative Example 1
[0080] Compared with Example 1, the difference is that no formamide auxiliary agent is added during the synthesis process.
[0081] A method for preparing a nickel-iron hydrotalcite adsorbent comprises the following steps:
[0082] S1, vent air through water with nitrogen for 30 min while heating to 80°C.
[0083] S2, using nickel nitrate and iron nitrate to prepare Ni 2+ and Fe3+ The molar ratio is 3:1, Ni 2+ and Fe 3+ The mixed solution with a total concentration of 0.5 mol / L was purged with nitrogen for 0.5 h.
[0084] S3, according to a volume ratio of 1:1, the mixed solution was dripped into the water from which air had been exhausted, and 2.5M sodium hydroxide solution was added to adjust the pH value of the system to 10, and nitrogen was maintained. After the reaction was maintained at 80°C for 10 minutes, the precipitate was separated by centrifugation, and the centrifuged sample was washed alternately with ethanol and deionized water, and dried at 80°C overnight to obtain a nickel-iron hydrotalcite adsorbent. Its XRD, FTIR and TEM results are as follows: Figure 1 , Figure 2 , Figure 3 shown.
[0085] Comparative Example 2
[0086] Compared with Example 1, the difference is that nitrogen is not passed through the reaction system to exhaust air during the synthesis process.
[0087] A method for preparing a nickel-iron hydrotalcite adsorbent comprises the following steps:
[0088] S1, prepare a 5.8 mol / L aqueous solution of formamide and heat it to 80°C.
[0089] S2, using nickel nitrate and iron nitrate to prepare Ni 2+ and Fe 3+ The molar ratio is 3:1, Ni 2+ and Fe 3+ The total concentration of the mixed solution is 0.5 mol / L.
[0090] S3, according to the volume ratio of 1:1, the mixed solution was dripped into the formamide aqueous solution, and 2.5M sodium hydroxide solution was added to adjust the pH of the system to be stable at 10, nitrogen was maintained, and the temperature was kept at 80°C for 10 minutes, and then the precipitate was separated by centrifugation. The centrifuged sample was washed alternately with ethanol and deionized water, and dried at 80°C overnight to obtain a nickel-iron hydrotalcite adsorbent. Its XRD, FTIR and TEM were as follows Figure 1 , Figure 2 , Figure 3 shown.
[0091] The morphology and performance of the porous nickel-iron hydrotalcite adsorbent prepared by the present invention were characterized. Since the morphology and fluorine removal performance of the porous nickel-iron hydrotalcite adsorbent prepared in Examples 1 to 6 of the present invention are similar, Example 1 is used as an example to illustrate the effect. The results are as follows.
[0092] 1. Morphological characterization and analysis
[0093] Depend on Figure 1It can be seen that there is no obvious difference in the XRD results of the nickel-iron hydrotalcite adsorbent prepared by adding amide molecules (Example 1) and without adding amide molecules (Comparative Example 1); while the (003) peak position of the nickel-iron hydrotalcite adsorbent prepared without nitrogen evacuation (Comparative Example 2) is significantly shifted to the left, mainly because the carbonate or bicarbonate formed by the dissolution of carbon dioxide in the air in water has a larger ionic radius and is more likely to enter the hydrotalcite as an interlayer anion.
[0094] Depend on Figure 2 It can be seen that there is no obvious difference in the FTIR results of the nickel-iron hydrotalcite adsorbent prepared by adding amide molecules (Example 1) and without adding amide molecules (Comparative Example 1); while the nickel-iron hydrotalcite adsorbent prepared without nitrogen evacuation (Comparative Example 2) has an obvious characteristic peak of CO3 functional group.
[0095] Depend on Figure 3 It can be seen that Figure 3 Figure a shows the TEM morphology of hydrotalcite at a lower magnification, and Figure b shows the TEM morphology of hydrotalcite at a high magnification. The background of the area indicated by the dotted circle has a large contrast with the surrounding area, corresponding to the pore structure on the hydrotalcite lamellae. Further high-resolution observation of the red and yellow local rectangular areas revealed that the lattice fringes at b1 and b2 both correspond to porous nickel-iron hydrotalcite adsorbents.
[0096] 2. Fluoride removal parameter influence test and fluoride removal application of porous nickel-iron hydrotalcite
[0097] Prepare 10 mg / L NaF aqueous solution, adjust the pH of the solution by dropping 1M NaOH or 1M HCl solution, add 2 g / L hydrotalcite into 20 ml NaF solution, and perform adsorption experiment in a plastic centrifuge tube at 30°C constant temperature oscillator for 6 hours to investigate the effect of pH value on the fluoride removal rate of hydrotalcite. Figure 4 shown.
[0098] Figure 4 The results show that at a near-neutral pH of 6, a high fluorine removal rate can be achieved. As the acidity continues to increase, the fluorine removal rate does not increase significantly, so this pH value can be selected in practical applications. In contrast, it is difficult for traditional defluorinators to achieve such a high fluorine removal rate under near-neutral conditions.
[0099] When investigating the dosage of hydrotalcite, the initial solution pH was fixed at 6, and other parameters remained unchanged, such as Figure 5 shown.
[0100] Figure 5The results show that when the amount of adsorbent is small, the defluorination efficiency increases rapidly, and when the amount of adsorbent is high, the defluorination efficiency tends to be flat; while the equilibrium adsorption capacity is gradually decreasing, mainly because as the amount of adsorbent increases, the active sites on the adsorbent surface gradually become redundant, so the adsorption capacity gradually decreases. Therefore, when studying the influence of various factors (pH, acid radical effect, initial fluoride ion concentration), in order to take into account both the defluorination efficiency and the adsorption capacity, the adsorbent dosage of 2g / L was selected.
[0101] When investigating the initial NaF solution concentration, the initial solution pH value was fixed at 6 and the hydrotalcite dosage was 2 g / L, and other parameters remained unchanged, such as Figure 6 shown.
[0102] Figure 6 The results show that fluoride ions are rapidly adsorbed in the first 25 minutes; after 25 minutes, the adsorption rate of fluoride slows down and then gradually reaches equilibrium; and the fluoride ion adsorption kinetics at each initial concentration are similar.
[0103] When investigating the effect of anions, the initial solution pH = 6 and the hydrotalcite dosage was 2 g / L, and different concentrations of acid anions were added at the same time, such as Figure 7 shown.
[0104] Figure 7 The results showed that in CO3 2- , HCO 3- PO4 3- , Cl - 、SO4 2- Among the five coexisting anions, CO3 2- , HCO 3- These are the two most significant anions, and their negative impact gradually increases with increasing concentration.
[0105] When conducting actual application tests, the amount of fluorine removal agent was adjusted from 2g / L to 5g / L, while other parameters remained unchanged, such as Figure 8 As shown. Figure 8 The results show that the porous nickel-iron hydrotalcite adsorbent of the present invention exhibits excellent defluorination activity in low-concentration, near-neutral fluoride-containing water bodies. The porous hydrotalcite defluorinator can reduce the fluoride ion concentration of 10 mg / L to 0.8 mg / L in near-neutral fluoride-containing water bodies, which is significantly better than the defluorination performance of commercial alumina defluorinators under the same conditions.
[0106] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing a porous nickel-iron hydrotalcite adsorbent, characterized in that: The following steps are involved: In a protective atmosphere, add soluble Ni to the amide aqueous solution at 50-95°C. 2+ Salt and soluble Fe 3+ The mixed solution of salts is prepared, the pH value is controlled to be 8-12, and an amide is used to perform an auxiliary coprecipitation reaction to obtain a porous nickel-iron hydrotalcite adsorbent.
2. The preparation method according to claim 1, characterized in that: Before the coprecipitation reaction occurs, the amide aqueous solution and the mixed solution are treated with nitrogen for ≥30 min.
3. The preparation method according to claim 1, characterized in that: The amide and soluble Ni 2+ Salt and soluble Fe 3+ The molar ratio of the sum of the salts is 2.5 to 50:
1.
4. The preparation method according to claim 3, characterized in that: The soluble Ni 2+ Salt and soluble Fe 3+ The molar ratio of the salt is 1 to 5:
1.
5. The preparation method according to claim 1, characterized in that: The coprecipitation reaction time is 5 to 20 minutes.
6. The preparation method according to claim 1, characterized in that: The soluble Ni 2+ The salt is nickel nitrate or nickel chloride, the soluble Fe 3+ The salt is ferric nitrate or ferric chloride; the amide is formamide, acetamide or N,N-dimethylformamide.
7. The preparation method according to claim 1, characterized in that: The pH value was controlled using NaOH solution.
8. The preparation method according to claim 1, characterized in that: After the coprecipitation reaction is completed, centrifugation is performed to obtain a primary product, which is washed with ethanol and deionized water, and dried at 70° C. to 80° C. to obtain a porous nickel-iron hydrotalcite adsorbent.
9. A porous nickel-iron hydrotalcite adsorbent prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the porous nickel-iron hydrotalcite adsorbent according to claim 9 in removing fluoride ions from water.